Canagliflozin attenuates Parkinson’s disease and is associated with modulation of gut-inflammasome–brain axis in rats - Nada K. Gamal; Rafik Fakhry; Youmna Hatem; Engy Rashed; Reem Marzouk; Ahmed K. M. Bukr; Kerolos Safwat; Mohamed Mamdouh; Ahmed AbdElFatah; Abdelrahman Atallah; Heba Attia; Iriny M. Ayoub; et al. (Inflammopharmacology, 2026)
Recent evidence links gut dysbiosis and the gut-brain axis to the pathophysiology of Parkinson’s disease (PD), which is considered one of the most common neurodegenerative illnesses and is characterized by motor symptoms and a gradual loss of nigral dopaminergic neurons. Canagliflozin (CANA), a sodium–glucose cotransporter-2 inhibitor with emerging anti-inflammatory and antioxidant properties, has recently gained attention for its neuroprotective effects beyond glycemic control. This research aimed to examine the neuroprotective potential of CANA in a rat model of PD, focusing on its potential effect on the gut-inflammasome–brain axis. Rats were treated with rotenone (ROT) (2 mg/kg, subcutaneous) and/or CANA (20 mg/kg, oral) for 30 consecutive days. Behavioral assessment ( n = 13), biochemical assays ( n = 6), and histological and immunohistochemical analysis ( n = 3) were performed. Microbiome profiling ( n = 3) using 16S rRNA amplicon sequencing was conducted using three pooled fecal samples/group, with each pool prepared from fecal material collected from three rats and fecal metabolomic profiling ( n = 5) was performed to assess microbial metabolites. ROT intoxication caused significant motor impairments, including decreased locomotor activity, poor coordination, and increased catalepsy. Further histological examination demonstrated dopaminergic neuronal loss and α-synuclein aggregation in the substantia nigra and striatum. CANA treatment enhanced motor function, conserved neuronal integrity, and decreased α-synuclein accumulation. Moreover, ROT altered the gut microbiota with selective taxonomic shifts, including enriched abundance of Parabacteroides and Ruminococcaceae with depleted Prevotella -related taxa, in addition to fecal metabolite profile alteration. Consequently, it increased colonic oxidative stress and weakened tight junctions, all of which enhanced LPS translocation. This systemic endotoxemia generated oxidative stress, dyslipidemia, and NF-κB/NLRP3 inflammasome activation. Conversely, CANA restored gut microbial balance and their metabolites, and gut integrity, decreased LPS leakage, and reduced systemic and central oxidative stress and inflammation, preventing inflammasome activation and α-synuclein aggregation. Collectively, these findings suggest that CANA may exert neuroprotective effects in ROT-induced PD associated with modulating the gut-inflammasome–brain axis.

Retraction Note: Amelioration of thioacetamide-induced hepatic encephalopathy in rats by low-dose gamma irradiation - Mona Abd El-Latif El-Ghazaly; Engy Refaat Rashed; Ghada Mahmoud Shafey; Hala Fahmy Zaki; Amina Salem Attia (Environmental Science and Pollution Research, 2024)

Exercise enhances the effectiveness of vitamin D therapy in rats with Alzheimer’s disease: emphasis on oxidative stress and inflammation - Engy Medhat; Laila Rashed; Marwa Abdelgwad; Basma Emad Aboulhoda; Mohamed Mansour Khalifa; Shimaa Saad El-Din (Metabolic Brain Disease, 2020)

RETRACTED ARTICLE: Amelioration of thioacetamide-induced hepatic encephalopathy in rats by low-dose gamma irradiation - Mona Abd El-Latif El-Ghazaly; Engy Refaat Rashed; Ghada Mahmoud Shafey; Hala Fahmy Zaki; Amina Salem Attia (Environmental Science and Pollution Research, 2020)